2012
DOI: 10.1016/j.dnarep.2012.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of human DNA repair proteins important for aging and genomic stability using yeast genetics

Abstract: Model systems have been extremely useful for studying various theories of aging. Studies of yeast have been particularly helpful to explore the molecular mechanisms and pathways that affect aging at the cellular level in the simple eukaryote. Although genetic analysis has been useful to interrogate the aging process, there has been both interest and debate over how functionally conserved the mechanisms of aging are between yeast and higher eukaryotes, especially mammalian cells. One area of interest has been t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 165 publications
(174 reference statements)
0
5
0
Order By: Relevance
“…In recent years, several yeast-based assays have been developed to study the biological function of human genes involved in breast, ovarian, and colon cancers (Aggarwal & Brosh, 2012;Millot et al, 2012;Rasmussen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several yeast-based assays have been developed to study the biological function of human genes involved in breast, ovarian, and colon cancers (Aggarwal & Brosh, 2012;Millot et al, 2012;Rasmussen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that among the large number of polymorphisms tested in this study, only a few functional SNPs could be conclusively identified with supporting evidence. These genes, which encode proteins that are involved in steroid action, cell cycle control and DNA repair pathways, are highly conserved [52,53], and therefore, the likelihood of finding common functional variants with a large effect on these genes is almost null due to the major role they play in the maintenance of the genomic integrity. Nonetheless, while small variations in the expression level of these genes might functionally impact their expression, transient transfection assays might not be the appropriate method to detect such small effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, construction of gene deletion strains, tagging proteins and site-specific mutagenesis are easier and faster than in human cells. Therefore, construction of "humanized" yeast, meaning a yeast strain expressing human genes or carrying mutation in an endogenous gene homologous to the human one, can be helpful in evaluating the functional consequences of human genetic variants found in several diseases [45][46][47][48]. When the yeast counterpart exists, functional assays can be developed by directly mutating the genomic copy of the yeast homologous gene ( Figure 1A).…”
Section: Yeast-based Functional Assays On Dna Repair Human Genesmentioning
confidence: 99%